BALANCE FAILURE IN SINGLE LIMB STANCE DUE TO ANKLE SPRAIN INJURY: AN ANALYSIS OF CENTRE OF PRESSURE USING THE FRACTAL DIMENSION METHOD. Issue 7 (11th March 2014) - Doherty, C; Delahunt, E; Bleakley, C; Hertel, J; Ryan, J; Caulfield, B
Abstract : Background: Dynamic stability is ubiquitous to fulfilling daily living activities. Instrumented postural control analysis plays an important role in evaluating the effects of injury on dynamic stability during balance tasks, and is often characterized with measures based on the displacement of the centre of pressure (COP) assessed with a force platform. However, the desired outcome of the task is frequently characterized by a loss of dynamic stability, secondary to injury. Typically, failed trials of balance tasks are discarded during research investigations. Objective: To compare the COP characteristics of failed trials in participants with acute lateral ankle sprain (LAS) to successful trial data in another group with the same injury, and a non-injured control group during a single limb stance (SLS) task. Design: Cross-sectional. Setting: University biomechanics laboratory. Participants: 29 participants with acute LAS attempted and succeeded a task of eyes closed SLS on their non-injured limb ( successful injured group ). A separate group of 28 participants with acute LAS attempted and failed the task on their injured limb ( failed injured group ). Finally a non-injured control group of 16 participants successfully completed the task on their non-dominant limb ( successful non-injured group ). Main outcome measure: Fractal dimension (FD) of the COP path during the SLS task. Results: There was a statistically significant difference at the level of P<.05 in FD scores for the three groups: F (2, 70)=11.61, P<.05 ( successful injured group =1.26±0.15= failed injured group : 1.17±0.14; successful non-injured group =1.38±0.11) with a large effect size. Conclusion: Successful eyes-closed SLS is characterized by a larger FD of the COP path trajectory when compared to failed trials, indicating greater utilisation of the available base of support.